An Analysis of Gender-Based Politeness Strategies in Gorontalo Oral Communication - Suleman, Amelia; Noor, Indah Rahmawati M; Abdussama, Nurfadila; Hela, Juneit R (Journal of Advance in Language, Literature, and Education, 2025)
The purpose of this study is to examine differences in male and female courtesy strategies in oral communication within the Gorontalo language community. This study uses qualitative approaches through extensive literature research and analyzes a variety of recent academic sources from sociolinguistics, practical application and linguistic anthropology. The analysis shows that women tend to use more indirect, more expressive and respectful language forms when communicating in general. In contrast, men with high probability are direct and assertive strategies in their speech. These differences are not only language decisions, but also reflect the underlying social structure and gender roles that exist in Gorontalo culture. Therefore, course strategies play an important role in maintaining social harmony and expressions of cultural identity related to all genders. By highlighting these distinctions, this study provides valuable insight into the functioning of language as a medium to reinforce social norms and gender expectations in a particular cultural context. Furthermore, research on the broader domain of gender-specific language studies is contributed by focusing on local Indonesian languages, which were often underrepresented in such discussions. Ultimately, this study enriches our understanding of how culturally embedded linguistic practices shape communication patterns and social relationships in Gorontalo society.